Financial management analysis of the management of operational assistance funds in Ra Almuta'alim, Galanggang village, Batujajar district, West Bandung - Siti Rodiah (Jurnal Scientia, 2024)
Education is a process to increase, improve, change knowledge, religion, intelligence and noble morals as well as the skills needed to support life. This research aims to determine the allocation of Operational Assistance Funds and how accountable the management of Operational Assistance Funds is. The problem that occurs in this research is that the main obstacle is the lack of funding sources. Only BOP funds are available, but the amount of funds received is not sufficient for needs, especially because the majority of students' parents are in the lower middle economic category. This research was conducted at the Ra Almuta'alim school agency. This research is classified as qualitative descriptive research, where the focus is on describing, recording, analyzing and interpreting findings through observation, interviews and documentation studies. The data analysis method in this research uses deductive and inductive. Based on the results of the research conducted, the author concludes that the use of operational assistance fund allocations requires careful monitoring of the use of operational assistance fund allocations at RA ALMUTAALIM. Transparency in reporting the use of funds needs to be increased to ensure that every expenditure related to operational activities carried out by RA Almuta'alim is based on the regulations for Management of Operational Assistance Funds for Providing Equal Education, namely, for Learning and Play, Support, and Fulfillment of Educational Unit Administration.